The Influence of Online Learning Workshops and Intrinsic Motivation On Teacher Performance in SD Al-Hidayah Majalengka - Vina Andita Pratiwi; Yeyet Daryati; Nur Alia Sumanti; Oktarina Adelia Putri; Yeyen Parlina (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study is to analyze the effects of e-learning workshops and intrinsic motivation on teacher effectiveness in Al Hidayah Primary School. The research method used quantitative research methods. Data collection techniques using questionnaire. The general population is 51 people and the sample is 6 people (deviation 5%). Data analysis methods used in this study include validity test, reliability test, classical hypothesis test (normality test, multicollinearity test and heteroskedasticity test), linear multiple regression analysis, hypothesis testing and coefficient of determination. The results of the study using SPSS 26.0 program calculations resulted in an f-number of 9.163, while the f-table was 3.209 and the R-square was 0.696. Thus, the independent variables, i.e. e-learning workshops and internal motivation, positively influence the dependent variable of the teacher's work efficiency by 69.6%.